An Aluminophosphate Molecular Sieve with 36 Crystallographically Distinct Tetrahedral Sites1. (26th May 2014) - Lee, Jun Kyu; Turrina, Alessandro; Zhu, Liangkui; Seo, Seungwan; Zhang, Daliang; Cox, Paul A.; Wright, Paul A.; Qiu, Shilun; Hong, Suk Bong
Abstract The structure of the new medium‐pore aluminophosphate molecular sieve PST‐6 is determined by the combined use of rotation electron diffraction tomography, synchrotron X‐ray powder diffraction, and computer modeling. PST‐6 was prepared by calcination of another new aluminophosphate material with an unknown structure synthesized using diethylamine as a structure‐directing agent, which is thought to contain bridging hydroxy groups. PST‐6 has 36 crystallographically distinct tetrahedral sites in the asymmetric unit and is thus crystallographically the most complex zeolitic structure ever solved.